Methods matter- construct validity of steps per day in patients with lumbar spinal stenosis - Gustafsson, Malin Eleonora av Kák; Schiøttz-Christensen, Berit; Wedderkopp, Niels; O’Neill, Søren Francis Dyhrberg; Brønd, Jan Christian (European Spine Journal, 2025)
Purpose: This study aimed to evaluate the ability of a thigh-worn accelerometer to detect walking during daily life in individuals with Lumbar Spinal Stenosis (LSS). Two hypotheses were made regarding how walking measurements from the accelerometer, a walking test, and an ankle-worn StepWatch would relate in order for the accelerometer to be valid. The hypotheses were: (a) there is no difference between the longest walk recorded by the accelerometer during daily life and the maximum walking duration in a walking test, and (b) the accelerometer agrees with the StepWatch in measuring total daily steps. Methods: This cross-sectional observational study on construct validity included 83 individuals with LSS who had a thigh-worn accelerometer for seven days and completed a walking test. Twenty-one also had an ankle-worn StepWatch simultaneously. Results: The duration of the longest walk recorded by the thigh-worn accelerometer and the walking test significantly agreed within an equivalence margin of 34%. The thigh-worn accelerometer recorded fewer steps per day than the ankle-worn StepWatch, Bland-Altman 95% limits of agreement at −162% to 35%, mean difference − 64%. Post hoc analysis showed agreement on step count during continuous walking, Bland-Altman limits of agreement at −7.1% to 1.8%, mean difference − 2.6%. Conclusion: The results suggest that a thigh-worn accelerometer can monitor continuous walking in daily life in individuals with LSS. The thigh-worn accelerometer did not agree with the ankle-worn StepWatch on daily steps. Device type and wear-site should be considered when interpreting step data.
Keywords: Accelerometer; Lumbar spinal stenosis; Monitoring; Neurogenic claudication; Validity; Walking; Walking test